Pentingnya Pekerja Kristus Dalam Implementasi Amanat Agung - Sostenis Nggebu (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
The problem studied in this article relates to the challenges and needs of Christ's workers to reap the yellowing fields. Remembering that the world as a field belonging to God is always short of workers. The response of church members to the challenges and needs allows the field to be reaped. The purpose of this article is to discuss the role of Christ workers in carrying out the Great Commission. The method used in this article is the hermeneutic method. The results show that the Christ worker is someone who surrenders and is actively involved in preaching the Gospel. Practically, he preaches the gospel, guides the people he serves to grow spiritually. In this case he is also known as a person who trains others to do the same task in carrying out the Great Commission of Jesus Christ.